2016
DOI: 10.1108/ccij-07-2015-0041
|View full text |Cite
|
Sign up to set email alerts
|

The framing and reframing of corporate financial results

Abstract: News agencies are important stakeholders for large organizations, since the news they distribute will be adopted by other news outlets, which influence public opinion and hence corporate reputation. This paper seeks to advance our understanding of how corporate earnings press releases are transformed into financial news by investigating whether the frames introduced by companies are adopted or reframed by news agencies. A content analysis of framing techniques in corporate earnings releases and their correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 68 publications
0
21
0
Order By: Relevance
“…Penrose (2008) notes that annual reports are often consulted when investors consider purchasing or selling the stock. Rosenkranz and Pollach (2016) note that journalists also rely on annual reports, but news media also “select and interpret corporate information when transforming corporate press releases into news reports” (p. 104).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Penrose (2008) notes that annual reports are often consulted when investors consider purchasing or selling the stock. Rosenkranz and Pollach (2016) note that journalists also rely on annual reports, but news media also “select and interpret corporate information when transforming corporate press releases into news reports” (p. 104).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Overall, qualitative research on the embeddedness of financial news has shown how the producers of financial news -companies, journalists and analysts -influence each other while depending on each other. Studies on financial news as the outcome of this embeddedness are few and far between, but have shown how journalists neutralize the promotional language of corporate press releases (Maat, 2007;Rosenkranz and Pollach, 2016). Furthermore, research in accounting has studied news produced by different actors, but has not compared them (Kothari et al, 2009) or even distinguished between them (e.g.…”
Section: The Embeddedness Of Financial Newsmentioning
confidence: 99%
“…News agencies face the same challenges, while being even more pressured to increase the speed of their reporting (Manning, 2012). Although this entails that journalists might have to rely on press releases for most of their stories (Goyanes and Rodríguez-Castro, 2019;Usher, 2017), they have been found to reframe promotional language from press releases by means of omissions, additions and changed valence (Maat, 2007;Rosenkranz and Pollach, 2016). However, there is little evidence about the tone of financial news produced by journalists.…”
Section: Tone In News Reportsmentioning
confidence: 99%
See 2 more Smart Citations